Bond behaviour between GFRP rods and concrete produced with seawater: an experimental research - Sena-Cruz, José (2018)
It is unquestionable that water is an indispensable natural resource for the existence of life on planet Earth, holding enormous environmental, economic and social value. Today, with the increase of the population and consequent increase in pollution, drinkable water is an increasingly sought-after and scarce resource. In this context, the need to explore the potential of the direct use of seawater in the production of reinforced concrete (RC) structures becomes evident. On the other hand, since the earliest times of universal history the sea constitutes the most important space in world economic development, to which onshore and offshore structures are associated. Structures when exposed to marine environments (e.g. ports, offshore structures, buildings located by the sea) are subjected to the simultaneous action of several physical and chemical deterioration processes that accelerate their degradation and greatly reduce their service life. With the advent of fibre reinforced polymers (FRP), the construction industry has experienced a revolution due to the countless advantages that these materials present, among which stands out their resistance to corrosion. Therefore, the use of these new materials in RC structures exposed to marine environments may prevent the main damages that aggressive agents typically originate in conventional RC, as well as to allow seawater to be directly used in the design of concrete, thus avoiding the use of drinkable water. In this work the possibility of using seawater in the design of RC structures, in combination to the use of glass FRP (GFRP) rods, is explored. The research carried out included two phases: (i) the development of concrete compositions including seawater and (ii) the assessment of the bond behaviour between GFRP rods and the developed concrete. The present part is mainly devoted to the second phase where the influence of type of water (tap water or seawater), the GFRP diameter and anchorage length on the bond between GFRP rods and concrete were investigated. The main results obtained have shown that the use of seawater in the concrete composition had no severe effects on the mechanical properties of the concrete and on the bond behaviour between the GFRP rods and the concrete.